E-WOM DAN PARIWISATA: SEBUAH TINJAUAN PUSTAKA SISTEMATIS - Pranaya , Astaf Aji; Sarjani , Dini Kumalawati; Rosalia , Fanny; Shabrina , Rahma Mesi; Shabrina , Rahma Mesi; Irwansyah , Irwansyah (JURNAL MASTER PARIWISATA, 2023)
Advances in technology affect consumer communication to influence other consumers through electronic word-of-mouth (e-WOM). Compared to commercial advertising, e-WOM is considered as a more credible source of information to influence purchasing decisions, especially in the tourism sector, which is an intangible sector. This study aims to provide a comprehensive description of the influence of eWOM and the tourism industry. To achieve this goal, a systematic literature review was conducted on 30 previous studies indexed by Scopus. From the results of this study, the definition of e-WOM is defined as positive or negative reviews from consumers regarding their experience consuming products or services published via the internet. Quantity, quality, trust, and credibility are e-WOM factors that affect a person's intention to visit a tourist destination. Meanwhile, the impact of e-WOM which consists of cognitive, affective, and normative also influences one's intention to visit. Satisfaction, comfort, and experience are the motivation for consumers to spread e-WOM. Keywords: e-WOM; tourism; systematic literature review.